Математическое моделирование пластинчатого конденсатора с переменным по длине сечением каналов - Арсеньева, Ольга Петровна; Капустенко, Пётр Алексеевич; Бабак, Татьяна Геннадиевна; Хавин, Геннадий Львович (НТУ "ХПИ", 2010)
The proposed plate for condenser has the heat transfer area that consists of several corrugated sections along its length. Shape and dimensions of ridges and valleys of corrugations are variable. The corrugations are inclined to plate vertical axis so the ridges of two adjacent plate corrugations are in contact. The channel formed by such plates has the variable cross-section area. The experimental study of heat transfer and pressure drop for channels of such pattern was carried out. The dependencies for film heat transfer and pressure drop were obtained for each channel part formed with adjacent sections of the plates. The obtained results were compared with those for plates which are conventionally used.
Keywords: гидравлическое сопротивление; пластина; алгоритм; теплообменный аппарат